STUDENT ACTIVISM IN POST-AUTHORITARIAN INDONESIA: HIGHER EDUCATION REFORM, MOVEMENT DYNAMICS, AND SHIFTING POLITICAL NARRATIVES - Ramadlan, Mohammad Fajar Shodiq; Aminuddin, Muhammad Faishal (JWP (Jurnal Wacana Politik), 2025)
This study investigates student activism in post-authoritarian Indonesia, focusing on the interplay between higher education reform, movement dynamics, and evolving political narratives over the past decade. Utilizing a mixed-methods approach, we surveyed 497 undergraduates from social and political science faculties at 26 Indonesian universities and supplemented our analysis with a document review of student movements from 1999 to 2021. The study examines the transformation of Indonesia’s higher education system, the defining characteristics of contemporary student activism, and the predominant socio-political issues driving post-authoritarian student movements. Our findings show that student activism primarily occurs through various platforms, including social media, organizational participation, public discourse, and street demonstrations. Strategic alliances between campus-based groups and external civil society actors have become increasingly important in facilitating these movements. These movements have increasingly focused on issues such as justice, civil liberties, and welfare, while the rise of anti-oligarchy sentiments highlights ongoing dissatisfaction with the unfinished process of democratic consolidation. The analysis further uncovers a shift in political narratives, reflecting the changing priorities of the student movement in response to Indonesia’s political evolution. This study offers valuable insights into the role of student activism in shaping the state’s post-authoritarian trajectory, contributing to the broader understanding of the youth movement in contemporary Indonesia.